WAHANA REKREASI ASTORIA WATERPARK DALAM FOTOGRAFI KORPORAT - Khalid Alhamda; Ivan Saputra (EZRA SCIENCE BULLETIN, 2026)
This final project, titled “Astoria waterpark Recreation Arena in Corporate Photography,” aims to strengthen the visual identity and brand image of Astoria waterpark as a premier tourist destination in Padang Pariaman Regency, West Sumatra, through a professional corporate photography approach. The creation process integrates theories of corporate photography, architectural photography, and lighting techniques specifically (available light, artificial light, and mixed lighting) to produce compelling and informative visual imagery. The project was executed through a structured methodology consisting of exploration, preparation, design, realization, presentation, and exhibition stages. The final output consists of 20 photographic works printed on matte-laminated photo paper in various sizes, exhibited as a form of corporate visual documentation that supports the destination’s branding and promotional strategies. This work is intended to serve as both an academic and practical reference for the development of corporate photography within a tourism context, while providing a significant visual contribution to the company in enhancing its appeal and public image.